Managing diversity: enhancing team experience in university community engagement (UCE) - A Manaf, Aini Maznina; Ahmad, Zeti Azreen (2019)
Community Engagement is prevalent in higher education institutions nowadays. Ideally, involvement in community engagement requires one to possess a strong teamwork spirit and skills to successfully achieve its goals. Addressing the issue of diversity in a team at workplace is crucial in the enhancement of teamwork spirit. Increasing demographic changes in organisations require people of different backgrounds to work together on a daily basis. As a result, it is common for groups and teams in organisations to be composed of members of different backgrounds. In a higher educational institution, working with academics of various disciplines in a community engagement projects are common. However, not much is known on the benefits of working in a diverse workgroups of community engagement projects. As such, this this study aims to explore how experiencing diversity in a workgroup enhances the researchers’ teamwork in community engagement projects. This study will employ qualitative methodology. Interviews with researchers involved in community engagement projects of a higher educational institution in Malaysia were carried out.